Efektifitas Pelatihan Kecerdasan Emosi untuk Meningkatkan Motivasi Diri pada Mahasiswa Berorganisasi di Universitas ‘Asiyiyah Yogyakarta - Annisa Warastri; Andhita Dyorita Khoiryasdien (Universitas Muhammadiyah Jember, 2022)
Student required to optimally contributed in social llife to fulfil the expectation and trust from community. Being active in organization was a form of the student contribution as agent of change. In this study, researchers will provide emotional intelligence training to several individuals that indicated has a low self-motivation. There are 30 subjects to be examined in this study that will be randomly selected. Then, the subject will be given emotional intelligence training for approximately 5 meetings.The result of this study show that there is self-motivation improvement by the research subjects after being given emotional intelligence training, which was indicated by an increase in the post-test score on the subject when compared to the score in the pre-test, from score value of 56 to 74. With this change in score value it means that emotional intelligence training effective in increasing self- motivation in research subjects.